2013
DOI: 10.4142/jvs.2013.14.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Expression and lytic efficacy assessment of theStaphylococcus aureusphage SA4 lysin gene

Abstract: Treatment of bovine mastitis caused by Staphylococcus (S.) aureus is becoming very difficult due to the emergence of multidrug-resistant strains. Hence, the search for novel therapeutic alternatives has become of great importance. Consequently, bacteriophages and their endolysins have been identified as potential therapeutic alternatives to antibiotic therapy against S. aureus. In the present study, the gene encoding lysin (LysSA4) in S. aureus phage SA4 was cloned and the nucleotide sequence was determined. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Thus, the application of lytic phage in single dose proved to be innovative and effective therapy for treatment of septic chronic wounds. Our findings related with bacteriophage therapy showed agreement with the findings of other workers like Slopek et al (1987); Alisky et al (1998);Mathur et al (2003);W ills et al (2005); Mishra et al (2012) and Breyne et al (2017) they reported the success in bacteriophage therapy was 60-100% against suppurative infections and abscesses. Bacteriophage may be inducing IFN gamma and some other interferon's which leads to good healing process.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, the application of lytic phage in single dose proved to be innovative and effective therapy for treatment of septic chronic wounds. Our findings related with bacteriophage therapy showed agreement with the findings of other workers like Slopek et al (1987); Alisky et al (1998);Mathur et al (2003);W ills et al (2005); Mishra et al (2012) and Breyne et al (2017) they reported the success in bacteriophage therapy was 60-100% against suppurative infections and abscesses. Bacteriophage may be inducing IFN gamma and some other interferon's which leads to good healing process.…”
Section: Resultssupporting
confidence: 92%
“…Phages lysates have been extensively used to prevent and treat many numbers of chronic septic bacterial infections with great recovery rate (Heo et al, 2009;Mishra et al, 2012 andBreyne et al, 2017). Present study was conducted to isolate, characterized and assess the antimicrobial activity of phage lysate in chronic septic wounds.…”
Section: Bacteriophages: a Potential New Therapeutic Alternate To Antmentioning
confidence: 99%
“…Numerous effective lysins derived from various species (Streptococcus pneumoniae, S. pyogenes, S. agalactiae, Staphylococcus, etc.) have been reported in recent years (30,31,(38)(39)(40). However, only three S. suis phage lysins (PlySs1, PlySs2, and LySMP) have been reported (24,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…They parasitize only host cells that are susceptible to infection, so they can be used as ideal antibacterial biological agents to replace antibiotics [8]. With the use of antibiotics, the problem of resistant bacteria is becoming increasingly serious; therefore, there is an urgent need for phage-derived products (endolysins) and phages to replace antibiotic drugs [9,10]. A number of phages PVS-1, PVS-2, PVS-3 and vB_VspP_pVa5, that infect V. splendidus have been reported, and their possess the efficacy to inactivate V. splendidus, the cultures infected with PVS-1, PVS-2, PVS-3 and vB_VspP_pVa5 at a MOI of 10 started to show significant decreases in optical density (OD 600 ) compared with the control culture at 3 h after infection (P < 0.05) [11].…”
Section: Introductionmentioning
confidence: 99%